Zinc Deficiency in Patients of Chronic Hepatic Encephalopathy - Shabana Lakho, Prem Kumar, . Ehsan Rahim Memon (Journal of Rawalpindi Medical College, 2018)
Background : To determine the zinc deficiency in patients with chronic hepatic encephalopathy Methods: In this cross section study decompensated hepatic cirrhosis diagnosed patients (n=102) aged>16 years,both gender, with hepatic encephalopathy as per its grades were included. Blood samples were drawn and serum zinc levels were estimated. Results: Mean-age of patients was 51.5±9.5 years. Men (64.7%) constituted the main. Zinc deficiency was noted in 68.6% patients. Hepatic encephalopathy grade II was most common (42.2%) . Hepatic encephalopathy grading, II, III and IV were found significantly associated with zinc deficiency (p-value= 0.007). No significant difference was found in zinc deficiency according to age p-value 0.739. Zinc deficiency was significantly higher among males (p-value 0.043). Conclusion: Zinc deficiency was quite high (68.6%),with hepatic encephalopathy. Zinc deficiency was more common in males and middle age group patients.